Improving Administrative Efficiency Through Training in Automated Letter Creation for the Staff of the Kantor Kampung Maredan Barat - Yenny Hosanna; Viona Rossalia; Yulia Ariani; Putri Arum; Rika Fitri Ramadani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Administrative efficiency through training in automated letter creation is a study aimed at maximizing output to reduce resource workload, yielding more optimal results to achieve organizational goals. This research employs a qualitative method with data collection through observation. The results show that the training enhances the effectiveness of letter creation and compilation, making the process faster, neater, and more consistent. However, challenges remain, such as difficulties in implementing the system due to the prior use of the Srikandi application at the Maredan Barat Village Office and a lack of staff motivation and creativity. In conclusion, automated letter creation training is a positive step in improving administrative efficiency and public service quality at the Maredan Barat Village Office, though further efforts are needed to address system adaptation issues and boost staff motivation and creativity.